An Empirical Evaluation of FASB 33: Financial Reporting and Changing Prices (Book). - Van Breda, Michael F.; Meyer, Philip E. (The Accounting Review, 1983)
Reviews the book "An Empirical Evaluation of FASB 33: Financial Reporting and Changing Prices," by Jalaleddin Soroosh Joo.